2003
DOI: 10.1038/sj.bjc.6600846
|View full text |Cite
|
Sign up to set email alerts
|

No excess risk of colorectal cancer among alcoholics followed for up to 25 years

Abstract: We conducted a population-based retrospective cohort study among 179 398 Swedish patients hospitalised for alcoholism from 1970 to 1994, and found no excess risk for colorectal cancers, overall or at any anatomical subsite. Our findings challenge the hypothesis that alcohol intake is a risk factor for cancer of the large bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In other study, alcohol intake was not associated with colon cancer risk. 18 These reports have not been inconclusive in the association between development of adenoma and alcohol intake until now.…”
Section: Discussionmentioning
confidence: 98%
“…In other study, alcohol intake was not associated with colon cancer risk. 18 These reports have not been inconclusive in the association between development of adenoma and alcohol intake until now.…”
Section: Discussionmentioning
confidence: 98%
“…Alcohol consumption in relation to CRC risk remains controversial, with some studies reporting a positive association (86)(87)(88), whereas others do not (89,90). Jacobson et al (91) reported that there was no association found between alcohol intake and adenoma recurrence in a case-control study comparing 186 recurrent polyp cases with 330 controls.…”
Section: Alcoholmentioning
confidence: 96%
“…14,15 The association between alcohol consumption and colorectal cancer is not conclusive, as some reports have shown an increased risk and others no excess risk. [16][17][18][19][20] Given the possible association between alcohol consumption and colorectal cancer, polymorphisms in the XRCC1 gene, which have the potential to alter the structure of DNA repair enzyme, could affect the risk of colorectal cancer in alcohol drinkers.We conducted a hospital-based case-control study of colorectal cancer in Incheon, South Korea, where the age-adjusted incidence rates were 27.0 among men and 17.5 among women per 100,000 person-years during the period 1997-2000. 2 To elucidate the role of the XRCC1 gene polymorphisms in colorectal cancer development, we carried out genotype association analyses.…”
mentioning
confidence: 99%